Climate change accelerates growth of urban trees in metropolises worldwide. Issue 1 (December 2017) - Pretzsch, Hans; Biber, Peter; Uhl, Enno; Dahlhausen, Jens; Schütze, Gerhard; Perkins, Diana; Rötzer, Thomas; Caldentey, Juan; Koike, Takayoshi; Con, Tran; Chavanne, Aurélia; Toit, Ben; et al.
Abstract Despite the importance of urban trees, their growth reaction to climate change and to the urban heat island effect has not yet been investigated with an international scope. While we are well informed about forest growth under recent conditions, it is unclear if this knowledge can be simply transferred to urban environments. Based on tree ring analyses in ten metropolises worldwide, we show that, in general, urban trees have undergone accelerated growth since the 1960s. In addition, urban trees tend to grow more quickly than their counterparts in the rural surroundings. However, our analysis shows that climate change seems to enhance the growth of rural trees more than that of urban trees. The benefits of growing in an urban environment seem to outweigh known negative effects, however, accelerated growth may also mean more rapid ageing and shortened lifetime. Thus, city planners should adapt to the changed dynamics in order to secure the ecosystem services provided by urban trees.